Analysis of the Application of Good Agricultural Practices (GAP) and the Factors Influencing It Among Independent Oil Palm Smallholders in Aceh Tamiang Regency - Nabila, Tasya; Iskandar, Elvira; Hakim, Lukman (Danadyaksa: Post Modern Economy Journal, 2026)
The implementation of Good Agricultural Practices (GAP) is a crucial component in meeting the sustainability standards for Indonesian Sustainable Palm Oil (ISPO) certification, which is mandatory for all oil palm industry players, including independent smallholders. As one of the regions with the largest oil palm plantations in Aceh, Aceh Tamiang Regency still faces challenges in GAP implementation due to low technical knowledge, weak institutional support, and limited access to information. This study aims to analyze the factors influencing farmers' perceptions of GAP, as well as identify the obstacles and the actual conditions of its implementation at the smallholder level. The research employed a quantitative method with a survey approach, involving 144 farmers from 18 farmer groups selected through Multistage Quota Sampling. Primary data were collected using a Likert-scale questionnaire and interviews, while secondary data were obtained from relevant institutional documents and scientific literature. The results indicate that farmer characteristics (β = 0.358), institutional support (β = 0.373), and access to information (β = 0.375) have a significant influence on farmers' perceptions of GAP. The main obstacles to GAP implementation include limited technical capacity, insufficient mentoring, and uneven access to information.